2021
DOI: 10.1186/s12873-021-00433-3
|View full text |Cite
|
Sign up to set email alerts
|

Management quality indicators and in-hospital mortality among acute coronary syndrome patients admitted to tertiary hospitals in Ethiopia: prospective observational study

Abstract: Background Acute coronary syndrome (ACS) remains the leading cause of cardiovascular disease mortality and morbidity worldwide. While the management quality measures and clinical outcomes of patients with ACS have been evaluated widely in developed countries, inadequate data are available from sub-Saharan Africa countries. So, this study aimed to assess the clinical profiles, management quality indicators, and in-hospital outcomes of patients with ACS in Ethiopia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
(28 reference statements)
6
5
1
Order By: Relevance
“…In this study, the mean age of ACS patients who presented to the ED was 54.65 ± 14.45 years. This was comparable with other studies in developing world like Gulf RACE registry (56.4±13years) [8], Indian study (56.06±11.29years) [9], the African INTERHEART study (54.3±11.3years) [10] and with other study from Ethiopia such as a multicenter study done at St. Peter's hospital and Jimma University (55.8±11.9 years) [11]. It was also found to be five years lower than that of the study done at Ayder Hospital in Mekelle, Ethiopia(59.12±12.98years) [12] and significantly older than a study done in Dakar, Senegal(34±1.9years) [13].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the mean age of ACS patients who presented to the ED was 54.65 ± 14.45 years. This was comparable with other studies in developing world like Gulf RACE registry (56.4±13years) [8], Indian study (56.06±11.29years) [9], the African INTERHEART study (54.3±11.3years) [10] and with other study from Ethiopia such as a multicenter study done at St. Peter's hospital and Jimma University (55.8±11.9 years) [11]. It was also found to be five years lower than that of the study done at Ayder Hospital in Mekelle, Ethiopia(59.12±12.98years) [12] and significantly older than a study done in Dakar, Senegal(34±1.9years) [13].…”
Section: Discussionsupporting
confidence: 89%
“…The use of guideline-directed in-hospital and discharge medications such as aspirin, second antiplatelet (clopidogrel), statins, beta-blockers, and ACEIs was almost comparable to that of other studies (17,18,21,24,30). However, as we have described in our previous study (14), a timely initiation of these guidelinedirected medications still needs improvement. During the first 24 h of hospital admission, patients presenting with STEMI more likely received guideline-directed medications compared to those who presented with NSTE-ACS.…”
Section: Discussionsupporting
confidence: 77%
“…ACS was diagnosed by treating cardiologists based on the third universal definition of myocardial infarction (13). Patients who died before evaluation and confirmation of ACS diagnosis, readmitted patients (enrolled previously), those who declined informed consent, and those unable to attend the 30-day follow-up were excluded from this study, as previously described (14). Therefore, the patient profiles in the present findings share similarities with previously published articles of the same project.…”
Section: Study Populationmentioning
confidence: 73%
“…The study showed that the median age of patients was 60 years, males were dominated, hypertension and diabetes mellitus patients were the common risk factors, and these findings were similar to previous Sudanese studies. 2 , 17 The mean age in the present study was higher than studies conducted in neighboring countries, 18 , 19 and significantly lower than the European population. 20 About clinical diagnosis of ACS, 58.4%, 22.5%, or 19.1% of patients in this study were diagnosed with STEMI, UA, or NSTEMI, respectively, which was consistent with the previous studies.…”
Section: Discussioncontrasting
confidence: 53%
“…13 , 14 Moreover, the study showed that 3.1% of patients died before hospital discharge, which was much lower than previously published reports from Egypt and Ethiopia. 18 …”
Section: Discussionmentioning
confidence: 99%